Pengaruh Perceived Price Dan Country Of Origin Terhadap Repurchase Intention Merek Minuman Xing Fu Tang Di Jakarta: Word Of Mouth Sebagai Variabel Mediasi - Lucas Kevin; Miharni Tjokrosaputro (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2021)
The purpose of this research is to examine whether 1) perceived price can effect repurchase intention. 2) perceived price can effect word of mouth. 3) country of origin can effect repurchase intention. 4) word of mouth can effect repurchase intention. 5) word of mouth mediates the effect perceived price on repurchase intention. Sample was selected using convenience sampling method amounted to 200 respondents. The result of this study show that perceived price and country of origin have not significant influence on repurchase intention, perceived price has significant influence on word of mouth, word of mouth has significant influence on repurchase intention, and word of mouth mediates the influence of perceived price on repurchase intention.Tujuan dari penelitian ini adalah untuk menguji apakah 1) perceived price dapat mempengaruhi repurchase intention. 2) perceived price dapat mempengaruhi word of mouth. 3) country of origin dapat mempengaruhi repurchase intention. 4) word of mouth dapat mempengaruhi repurchase intention. 5) word of mouth memediasi pengaruh perceived price terhadap repurchase intention. Sampel dipilih menggunakan metode convenience sampling berjumlah 200 responden. Hasil dari penelitian ini menunjukkan bahwa perceived price dan country of origin tidak memiliki pengaruh yang signifikan terhadap repurchase intention, perceived price memiliki pengaruh yang signifikan terhadap word of mouth, word of mouth memiliki pengaruh yang signifikan terhadap repurchase intention, dan word of mouth dapat memediasi pengaruh perceived price terhadap repurchase intention.